Hypersonic control effectiveness - Kumar, D. (Cranfield University, 1995)
The present study analyses the effects of a number of geometric parameters on the performance of a trailing edge control flap on a hypersonic body. The tests were conducted in a gun tunnel at Mach 8.2 and Mach 12.3. The study revealed that flap deflection promoted separation lengthscales and boundary layer transition. The latter significantly increased the local aerothermal loads on the flap. For well separated flows, flap heat transfer rates were successfully predicted by reference temperature theory. The promotion of transition caused a progressive reduction in the lengthscales of separated flows. In a free-flight environment, vehicle incidence varies considerably. Incidence was found to promote transition on both flat plates and control flaps. The latter resulted in a considerable increase in flap heat transfer. A modified version of reference temperature theory successfully predicted the aerothermal loads on the flap. For laminar and transitional interactions, the separated flow lengthscale was found to have a complex variation with incidence. A number of relevant flow parameters were identified. The intense heat loads on a vehicle in hypersonic flight dictates the blunting of the leading edge. This strengthens the leading edge shock structure and generates an entropy layer. Bluntness was found to significantly decrease the separation interaction scales on the flap. This was due to a reduction in the pressure recovered on the flap. The latter adverse affects control effectiveness. The aerothermal loads on the control flap was successfully predicted by reference temperature theory. An investigation into the efficiency of an under-expanded transverse jet controls was conducted on an axi-symmetric slender blunt cone. Force measurements found that the interaction augmented the jet reaction force by 70% at zero incidence. This increased to 110% at low incidence. The experiments found that the scale of the interaction region was determined by Poj/pes. Using this parameter, a closed loop algorithm for the shape of the separation front was developed. The latter can be used to predict jet reaction control effectiveness.